2012
DOI: 10.1080/1059924x.2012.626750
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Exploration of Excessive Daytime Sleepiness, Depression, and Musculoskeletal Pain among Migrant Farmworkers

Abstract: In this study the authors estimated the prevalence of elevated daytime sleepiness, depressive symptoms, and musculoskeletal pain among Latino migrant farmworkers, and examined the relationship among these symptoms. Data are from a cross-sectional survey of migrant farmworkers (300) conducted in eastern North Carolina in 2009. Results Eleven percent of Latino farmworkers reported elevated levels of daytime sleepiness, 28% reported elevated levels of depressive symptoms, and 5% reported moderate to severe muscu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 55 publications
4
45
1
2
Order By: Relevance
“…5,73,131 Consistent with this exposure, HAs report more occupational pain and injury than NHWs. 36,129 Numerous investigations have found that acute and chronic pain is a common complaint among HA workers employed in agriculture, 8,19,60,88,110,117,121,135 construction, 5,21,52 and the service industry. 48,52,56 Furthermore, a survey of 300 HA farmworkers with musculoskeletal pain found that 28% were above the CES-D clinical cut point for depression.…”
Section: Experience Of Painmentioning
confidence: 99%
See 1 more Smart Citation
“…5,73,131 Consistent with this exposure, HAs report more occupational pain and injury than NHWs. 36,129 Numerous investigations have found that acute and chronic pain is a common complaint among HA workers employed in agriculture, 8,19,60,88,110,117,121,135 construction, 5,21,52 and the service industry. 48,52,56 Furthermore, a survey of 300 HA farmworkers with musculoskeletal pain found that 28% were above the CES-D clinical cut point for depression.…”
Section: Experience Of Painmentioning
confidence: 99%
“…48,52,56 Furthermore, a survey of 300 HA farmworkers with musculoskeletal pain found that 28% were above the CES-D clinical cut point for depression. 121 Among HAs working in manual labor and agricultural occupations, awkward posture and repetitive movements predicted higher rates of low back pain. 60 …”
Section: Experience Of Painmentioning
confidence: 99%
“…The neuromuscular and perceptual fatigue created by consecutive days of tournament play can create impairments in sprinting and jumping ability, and biochemical markers of muscle damage and reduced mood states [17], all of which may reduce the athlete's ability to move and land optimally. Similarly, in relation to more cognitive factors, mental fatigue has been shown to impair intermittent running performance [18], with depressive symptoms and daytime sleepiness positively associated with musculoskeletal injury [19]. Furthermore, sleep disturbance was found to be signi icantly related to work related injuries by Uehli et al [20].…”
Section: Relationship Issues 12% (2 Out Of 17)mentioning
confidence: 99%
“…Sleep disorders, such as untreated obstructive apnea and insomnia, are associated with an increased risk of workplace injury [1–3], physical health problems [4–6], musculoskeletal pain, depression, and anxiety [7–12]. Limited information is available about sleep quality and the prevalence of sleep disorders among the Latino population [13–16]; substantially less is known about the sleep quality of Latino farmworkers [12, 17]. Twenty percent of Latino farmworkers in Texas report poor sleep quality [18].…”
Section: Introductionmentioning
confidence: 99%